Perceived effectiveness of email versus face-to-face communication for internal briefings amongst Blue Moon teams - Naidoo, Aleeshia (The IIE, 2020)
The researcher’s aim for this study was to determine employee perceptions on the effectiveness of email communication versus face-to-face communication when having to internally brief their team members at Blue Moon Corporate Communications (BM). The researcher completed a qualitative study conducting semi-structured interviews with employees in the Employee Alignment Division at BM. The goal was to interpret and understand employee perceptions of effective communication and to gain an understanding of whether employees perceived one medium of communication more sufficient than the other to achieve effective communication. Qualitative data analysis was conducted and the findings indicated that BM employees place a high worth on effective communication that is concrete, concise and complete when internally briefing their team members. This theme and subtheme were mentioned the most. The results challenged the majority of the current literature which argue in favour of electronic communication as a more effective means of communication than face-to-face communication, of which BM employees perceive face-to-face communication to be a time-saving activity due to the richness the medium provides. Email communication was perceived as time-consuming because of its written form. This result was not expected and creates heuristic value for future studies.
Keywords: Email communication; Face-to-face communication; Effective communication; Small group communication; Team/internal briefings; Media richness; Employee perceptions